REPRESENTASI ETNOKULTURAL DALAM GEGURITAN BOJONEGORO: KAJIAN SASTRA KEWILAYAHAN - Mashuri Mashuri (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. This study examines construction variety of ethnocultural in geguritan Bojonegoro by Pamarsudi Sastra Jawi Bojonegoro (PSJB) which are compiled in Bojonegoro Ing Gurit (2006). The approaching is literature and cultural study and the writer as a agent. In history, penggurit (the writer of the Guritan) reveal and observe the condition of Bojonegoro in different and complement language and idiom representation to present construction of Bojonegoro complexly. Bojonegoro is presented here not as beautiful, harmony, and missed village, nevertheless it present its the tragic and dark side. In nowadays context, the documentation of the result of penggurit in this long duration can be a barometer to know the existence of Bojonegoro now, because the available guritan store documentative aspect and history record. Moreover, penggurit are cultural agent that cannot be separated from the habit of manifesting its cultural practice in the gurit writing field, that are proven by forming a Java literature composing organization, named PSJB and admission and achievement acquisition for that organization and its exponent. Keywords: Regional literature, gurit Bojonegoro, ethnocultural documentation